Opioid use patterns in patients with head and neck cancer receiving radiation therapy: Single‐institution retrospective analysis characterizing patients who did not require opioid therapy. Issue 10 (18th June 2021) - Rich, Benjamin J.; Schumacher, Leif‐Erik D.; Sargi, Zoukaa B.; Masforroll, Melissa; Kwon, Deukwoo; Zhao, Wei; Rueda‐Lara, Maria A.; Freedman, Laura M.; Elsayyad, Nagy; Samuels, Stuart E.; Abramowitz, Matthew C.; Samuels, Michael A.
Abstract: Background: We had previously analyzed the variables that determine the rates of opioid use at 1‐year postradiotherapy in patients with head and neck cancer. Here we analyze the variables associated with opioid abstinence during and in the 12 months after radiotherapy at our institution. Methods: We identified a cohort of patients with head and neck cancer who received radiotherapy as part of curative treatment at our institution. Logistic regression analyses were performed to determine socioeconomic and clinical factors associated with opioid abstinence. Results: The cohort included 376 patients. On multivariable analysis, patients from an upper‐income class ( p = 0.004), black race ( p = 0.004), older ( p = 0.008), with dependent children ( p < 0.001) or receiving surgery ( p = 0.002) were more likely to abstain from opioids, while patients using analgesic mouthwash ( p = 0.009) or higher pain scale ( p = 0.002) were less likely. Conclusion: Socioeconomic and treatment characteristics are associated with opioid abstinence during and following radiation treatment in patients with head and neck cancer.